Comparisons between POC and zooplankton swimmer flux from sediment traps in the subarctic and subtropical North Pacific. (March 2018) - Yokoi, Naoya; Abe, Yoshiyuki; Kitamura, Minoru; Honda, Makio C.; Yamaguchi, Atsushi
Abstract: Seasonal changes in zooplankton swimmer (ZS) abundance, biomass and community structure were evaluated based on samples collected by moored sediment traps at a depth of 200 m in the subarctic (SA) and subtropical (ST) western North Pacific. Based on these samples, we made comparisons on two topics: 1) latitudinal (subarctic vs. subtropical) changes in ZS abundance, biomass and community and 2) quantitative differences between the ZS and particle organic carbon (POC) fluxes based on data from moored or drifting sediment traps. The results showed that the ZS flux was greater in the SA (annual mean: 311 ind. m −2 day −1 or 258 mg C m −2 day −1 ) than in the ST (135 ind. m −2 day −1 or 38 mg C m −2 day −1 ). The peak ZS flux was observed from July–August in the SA and from April–May in the ST. The dominant taxa were Copepoda and Chaetognatha in the SA and Ostracoda and Mollusca in the ST. These latitudinal differences are likely related to the dominance of large-sized Copepoda in the SA, regional differences in the timing of the spring phytoplankton bloom, and the magnitude and size structure of primary producers. The percent composition of ZS to the total C flux (= ZS+POC flux) varied by region: 85–95% in the SA and 47–75% in the ST. These differences between the ZS composition and the total C flux are most likely caused by the dominance of large-sized Copepoda ( Neocalanus spp. and Eucalanus bungii ) in the SA. Highlights: Seasonal changes in zooplankton swimmer populations were studied by sediment traps at 200 m. Throughout the stations, zooplankton swimmer carbon was greater than the POC flux. Dominance of large-sized Copepoda was marked for the subarctic region.